Knockout of cadmium sensitive gene 1 confers enhanced cadmium tolerance in rice (Oryza sativa L.) by regulating the subcellular distribution of cadmium - Liang, Shanshan; Lan, Zhipeng; Wang, Jiahan; Zou, Wenli; Hu, Youchuan; Ran, Hongyu; Qin, Mao; Xiao, Gui; Zhang, Siju; Ma, Xuan; Ye, Guoyou; Luan, Weijiang (Elsevier, 2025)
Cadmium (Cd) is a heavy metal which is toxic to both plants and animal. The high content of Cd in the rice grain severely threatens human's health. Here, we identified a Cd sensitive gene, named Cadmium Sensitive Gene 1 (OsCSG1), playing an important role in improving Cd tolerance in rice at seedling stage. The expression of OsCSG1 was induced by CdCl2 and exhibited higher mRNA levels in leaf blade, leaf sheath and stele of roots. Knockout of OsCSG1 improved the Cd tolerance of rice seedlings, suggesting that OsCSG1 negatively regulated Cd tolerance in rice. The Cd concentration in roots of seedling of oscsg1 mutants increased significantly under Cd stress, but not in the shoot and grains compared with wild type (WT). Subcellular distribution of Cd in root cells suggested that Cd proportions in soluble fractions of cells in oscsg1 mutant increased significantly. And CAT activity in oscsg1 mutants increased significantly. Taken together, knocking out OsCSG1 could improve Cd tolerance in rice by regulating subcellular distribution of cadmium and increased CAT activity.